THE TAXES OF INTERWAR LITHUANIA FROM THE PERSPECTIVE OF THE MODERN LITHUANIAN TAX LAW - Burneikaitė, Indra (Teisė, 2017)
The concept, features, types, functions of taxes as well as tax burden applied to the profits of private companies in Interwar Lithuania are analyzed in this article from the perspective of the modern Lithuanian tax law.